Assemblages of creativity: Material practices in the creative economy - Duff, Cameron; Sumartojo, S. (The International Society for Organization Development, 2017)
This article questions the anthropocentrism of existing treatments of creative work, creative industries and creative identities, and then considers various strategies for overcoming this bias in novel empirical analyses of creativity. Our aim is to begin to account for the nonhuman, ‘more-than-human’, bodies, actors and forces that participate in creative work. In pursuing this aim, we do not intend to eliminate the human subject from analysis of creative practice; rather we will provide a more ‘symmetrical’ account of creativity, alert to both the human and nonhuman constituents of creative practice. We draw from Deleuze and Guattari’s discussion of the assemblage to develop this account. Based on this discussion, we will define the creative assemblage as a more or less temporary mixture of heterogeneous material, affective and semiotic forces, within which particular capacities for creativity emerge, alongside the creative practices these capacities express. Within this assemblage, creativity and creative practice are less the innate attributes of individual bodies, and more a function of particular encounters and alliances between human and nonhuman bodies. We ground this discussion in qualitative research conducted in Melbourne, Australia, among creative professionals working in diverse fields. Based on this research, we propose a ‘diagram’ of one local assemblage of creativity and the human and nonhuman alliances it relies on. We close by briefly reflecting on the implications of our analysis for debates regarding the diversity of creative work and the character of creative labour.